2019
DOI: 10.1016/j.rvsc.2019.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Current status and management of canine leishmaniasis in Latin America

Abstract: Latin America encompasses diverse geographical, cultural and socioeconomic conditions, which are reflected in the challenges for infectious disease control in the region. One of the most significant regional infectious diseases for humans and domestic dogs is leishmaniasis, occurring as visceral leishmaniasis (VL) caused by Leishmania infantum (syn. L. chagasi) transmitted by sand flies (Lutzomyia longipalpis) and with a canine reservoir, and the more common cutaneous leishmaniasis (CL) involving multiple Leis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
59
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 197 publications
0
59
0
2
Order By: Relevance
“…Domestic dogs are considered the main reservoirs of L. infantum, playing an important role in the epidemiology of VL (42,43). The number of infected dogs in South America is estimated in the millions, and there are high infection rates associated with a high risk of human disease (42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…Domestic dogs are considered the main reservoirs of L. infantum, playing an important role in the epidemiology of VL (42,43). The number of infected dogs in South America is estimated in the millions, and there are high infection rates associated with a high risk of human disease (42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…Canine visceral leishmaniosis (CVL) is widespread from Mexico to Argentina, with autochthonous cases reported in many countries. The number of infected dogs in LATAM is estimated in millions, and there are high infection rates, especially in Brazil (Marcondes & Day 2019). Most epidemiological studies are conducted using serology, but the application of PCR in endemic areas has confirmed that the prevalence of infection in dogs is much higher than the seroprevalence (Baneth et al 2008).…”
Section: Canine Visceral Leishmaniosismentioning
confidence: 99%
“…Most epidemiological studies are conducted using serology, but the application of PCR in endemic areas has confirmed that the prevalence of infection in dogs is much higher than the seroprevalence (Baneth et al 2008). The seroprevalence of CVL in endemic areas of Brazil ranges from 3.1 to 36.0% (Rosypal et al 2007, Belo et al 2017, Marcondes & Day 2019…”
Section: Canine Visceral Leishmaniosismentioning
confidence: 99%
See 1 more Smart Citation
“…Highest number of reports related to MIL, Sb V and allopurinol originated in Spain and Italy and in the case of AmB, these countries along were the most represented. The late introduction of MIL in the Brazilian market (Milteforan® was approved in 2016), together with active policies in favor of culling infected dogs in this country[35] could account for this relative scarcity of scienti c reports on MIL. The degree of aggregation with the other drugs was comparable although there were some striking ndings such as the presence of USA in AmB reports or Venezuela in MIL treatment of CanL.…”
mentioning
confidence: 99%